Factors Affecting the Motivation of the 21st Century Educators - Suson, Roberto; Anoos, Wilfredo; Mamites, Irene (International Journal of Psychosocial Rehabilitation, 2020)
The quality of teaching and learning is determined not just by the quality of teachers, but also the quality of the environment where they are working. This study aims to track the motivational factors of basic education educator. The results show that teachers are well motivated when they have an environment that support their way of life as a teacher. It also shows that teachers are well satisfied with their job security. On the one hand, their eagerness to improve and develop supports the previous studies that indicate the importance of intrinsic supports for their development.